THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE, COMPETENCE AND JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Rahmanto, Efendi; Aprillia, Juwita (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The reason of this study was to determine the effect of transformational leadership style, competence and job satisfaction both simultaneously or partially on organizational citizenship behavior case studies on lecturers on the Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta faculty of Economics. The sample in this take a look at have been all 36 lecturers. The assessments performed on this study used validity, reliability, classical assumptions, multiple regression, T test and F check using the SPSS 25.0 software application. The results confirmed that transformational leadership style, competence and activity satisfaction either partially or simultaneously have a effective and significant impact on organizational citizenship behavior.